Design and Fabrication of Solar Tricycle for Physically Challenged Persons - Prabakaran, V.; R. M., Sreenithi; G., Suresh; R., Tamilmani; V., Tamil Selvan (International Journal For Research In Mechanical & Civil Engineering, 2017)
Solar plays a vital role in our day to day life. We have developed the solar tricycle especially for handicapped person. In this paper it is discussed that how solar tricycle will help to reduce the effort of handicapped person. All the designs specification considered after analyzing the problems from the handicapped person. Comfort of the person in the tricycle is an important and we have given importance to it. The main content of the tricycle is Solar PV panel, Brushless PMDC motor, Charge controller and battery. This paper will discuss about the main idea of this project and to get a larger picture on what is the problem in the current technologies, what that I want to achieve in this project and the area that will cover on this project. This paper is divided into some categories that are project background to describe the reasons to do this project, problem statement to inform about the problem or weakness of the existing technology, objective to make sure what actually this project must achieve and scope of this project to specify what will be used in this project.